PENGARUH KETERAMPILAN, PENGETAHUAN DAN KEMAMPUAN SDM TERHADAP KINERJA KARYAWAN AGROINDUSTRI DANGKE DI KELURAHAN MATARAN KECAMATAN ANGGERAJA - Anwar Anwar; Aulia Nurul Izmi; Agung Widhi Kurniawan (Lafadz Jaya Publisher, 2023)
This objective of this research to determine the influence of skills, knowledge and human resources capabilities on the performance of dangke agro-industrial employees in the materi Village. In addition, this application can also be used to improve computer performance. The sample in this study using saturated sample techniques with the number of 30 respondents.This study was conducted using multiple lienar regression analysis. The results showed that there was a positive and significant influence on the overall ability, knowledge and ability of human resources on employee performance with a presentation of 91.1%. This shows the meaning that the dependent variable (employee performance) can be interpreted by the ability, knowledge and ability of human resources by 91.1%, while 8.9% (100% - 91.1%) is expressed by the cause and other factors that are under the variable ability, knowledge and ability of human resources studied. Such as aspects of salary or salary allowances (bonuses) required, work motivation to discipline individual employees in carrying out work in the agro-industry dangke Mataran Village.